2021
DOI: 10.3390/ijerph182412871
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Romanian Version of the Toronto Empathy Questionnaire (TEQ) among Undergraduate Medical Students

Abstract: Medical professionals require adequate abilities to identify others’ emotions and express personal emotions. We aimed to determine the validity and reliability of an empathy measuring tool in medical students for this study. We employed Spreng’s Toronto Empathy Questionnaire (TEQ) as a starting point for this validation. The process was performed in several steps, including an English-Romanian-English translation and a focus group meeting to establish each question’s degree of understandability and usability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The mean baseline TEQ score in our study (40.519±5.71) was comparable to a previous study (39.28±15.65) [ 14 ]. However, the mean baseline TEQ score was lower than studies conducted in other countries, such as the Caribbean and Romania, where the average baseline TEQ scores ranged from 45 to 50 [ 15 , 16 ]. This could be attributed to cultural and social differences or variations in the educational systems of these countries [ 17 ].…”
Section: Discussionmentioning
confidence: 65%
“…The mean baseline TEQ score in our study (40.519±5.71) was comparable to a previous study (39.28±15.65) [ 14 ]. However, the mean baseline TEQ score was lower than studies conducted in other countries, such as the Caribbean and Romania, where the average baseline TEQ scores ranged from 45 to 50 [ 15 , 16 ]. This could be attributed to cultural and social differences or variations in the educational systems of these countries [ 17 ].…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, Javaeed et al concluded that “Female students showed higher empathy than male ones for some IRI scale items” [ 103 ]. Ursoniu et al used the Toronto Empathy Questionnaire (TEQ) and found significantly higher empathy scores for female medical students compared to male medical students in convergent validity [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…This 16-item scale measures the general tendency to empathize with other people (“It upsets me to see someone being treated disrespectfully” and “I find that I am ‘in tune’ with other people’s moods”) [ 29 , 30 ]. Items are rated on a Likert scale from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Methodsmentioning
confidence: 99%